The Hidden Tragedy of Invisible Victims - Jacob M. Appel (Journal of Scientific Innovation in Medicine)
Medical policy makers often prioritizes visible victims—those whose harm is immediate and apparent—at the expense of invisible victims, individuals harmed indirectly by such a system. Using mandatory reporting laws as a case study, this commentary highlights how such policies can discourage diagnosis and treatment, ultimately increasing harm. Because these victims do not self-identify and their suffering is diffuse, the outcomes for these invisible victims are rarely measured. A cultural shift is needed in medicine and public health in order to both acknowledge and to account for these hidden casualties.